Metamaterial-enhanced coda wave interferometry with customized artificial frequency-space boundaries for the detection of weak structural damage. (15th July 2022) - Shan, Shengbo; Liu, Ze; Cheng, Li; Pan, Yongdong
Abstract: Coda wave interferometry (CWI), based on the accumulated scattered and reflected waves from scatterers and structural boundaries, has been shown to offer remarkable sensitivity to weak structural damage. However, coda waves highly rely on wave reflections from structural boundaries, which compromises the efficiency of the CWI for the monitoring of large structures. In addition, coda waves usually contain global damage information, thus hampering their use for damage localization. Targeting these problems, this work proposes a meta-device design to enhance the performance of the CWI. The deployment of the meta-device generates artificial frequency-space boundaries, which allow for an effective manipulation and customization of wave propagation in a selective manner in terms of both frequency content and inspection area. As a result, coda wave energy, alongside their interaction with structural damage, is enhanced, conducive to the detection of weak structural damage. Finite elements are carried out to evaluate the feasibility of the concept and to further explore the mechanisms and characteristics of the enhanced CWI. By synthesizing and combining multiple meta-devices with different bandgaps, a zone-by-zone damage detection and localization strategy is proposed. The proposed meta-device and damage detection strategy are finally validated through experiments. Results confirm that the proposed meta-devices significantly enhance the sensitivity of the CWI to weak damage and their potential for damage localization. The concept of metamaterial-assisted CWI shows great promise for future structural health monitoring applications.